T’ah kóó hóniidló, we’re still HERE! Mining legacies, Indigenous health and innovative solutions - Tsosie, Ranalda L. (Frontiers in Public Health, 2024)
In the world today, there are many unknowns especially with rising environmental concerns. However, one of the most important is an irreplaceable and shared resource, water or as the Diné (Navajo) refer to as, Tó. Throughout the world many Indigenous communities are facing water challenges, from lack of and access to adequate infrastructure, water rights, climate change and water contamination issues due to a variety of sources including anthropogenic sources like mining, especially, on the Navajo (Diné) reservation.This article aims to bring forth awareness of the long-standing water contamination issues in Diné communities and to shed light on innovative solutions being developed through current research efforts. Specifically, Dr. Tsosie's research aims to optimize a handheld point of use filter unit with a filter casing design that is customizable to a community and/or household through an easily removable and exchangeable cartridge system. Despite all the challenges and legacies of mining faced by not only Diné communities but many Indigenous communities, We Remain and We Are Still Here.